Akibat Hukum terhadap Penggunaan Air Bawah Tanah tanpa Izin - I Gusti Agung Gede Catra Artawan; I Nyoman Budiartha; I Nyoman Sutama (Jurnal Konstruksi Hukum, 2020)
Underground water is water that is contained in a layer of soil or rock below the soil surface. This study aims to determine the government's authority in regulating groundwater permits and what are the legal consequences of violating unlicensed groundwater use. The research was conducted using empirical legal research methods, source of the data which was used are primary and secondary sources of legal materials, methods of collecting legal materials using documentation studies and field research, and analyzing legal materials using descriptive analysis methods. The results of this study indicate that the Government's authority in permitting groundwater is regulated in the Bali Governor Regulation Number 5 of 2016 concerning Groundwater Permits, particularly in Article 3 paragraph (1), it is explained that the Governor has the authority to manage groundwater in CAT in the province. In Article 3 paragraph (2), the authority of the Government (Governor) is reaffirmed, including several things, namely: granting permits for groundwater drilling; give permission to extract groundwater; grant permits for the use of groundwater; granting permits for groundwater exploitation; grant permits to groundwater drilling companies; provide guidance, supervise technical investigations and use of Groundwater. As a result of violations of the use of groundwater by violating the parties in accordance with Article 15 paragraph (1) of Law Number 11 of 1974 concerning Irrigation, it is stated that anyone who deliberately runs water and / or water sources business without permission from the Government is punishable by imprisonment. 2 (two) years and or a maximum fine of Rp. 5,000,000 (five million rupiah).